DIFFERENTIATION BETWEEN Nocardia spp. AND Mycobacterium spp.: CRITICAL ASPECTS FOR BACTERIOLOGICAL DIAGNOSIS - Muricy, Edna Cleide Mendes; Lemes, Romilda Aparecida; Bombarda, Sidney; Ferrazoli, Lucilaine; Chimara, Erica (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
New methodologies were developed for the identification of Nocardia but the initial diagnosis still requires a fast and accurate method, mainly due to the similarity to Mycobacterium, both clinical and bacteriologically. Growth on Löwenstein-Jensen (LJ) medium, presence of acid-fast bacilli through Ziehl-Neelsen staining, and colony morphology can be confusing aspects between Nocardia and Mycobacterium. This study describes the occurrence of Nocardia spp. in a mycobacterial-reference laboratory, observing the main difficulties in differentiating Nocardia spp. from Mycobacterium spp., and correlating isolates with nocardiosis cases. Laboratory records for the period between 2008 and 2012 were analyzed, and the isolates identified as Nocardia sp. or as non-acid-fast filamentous bacilli were selected. Epidemiological and bacteriological data were analyzed as well. Thirty-three isolates identified as Nocardia sp. and 22 as non-acid-fast bacilli were selected for this study, and represented 0.12% of isolates during the study period. The presumptive identification was based on macroscopic and microscopic morphology, resistance to lysozyme and restriction profiles using the PRA-hsp65 method. Nocardia spp. can grow on media for mycobacteria isolation (LJ and BBL MGIT™) and microscopy and colony morphology are very similar to some mycobacteria species. Seventeen patients (54.8%) were reported and treated for tuberculosis, but presented signs and symptoms of nocardiosis. It was concluded that the occurrence of Nocardia sp. during the study period was 0.12%. Isolates with characteristics of filamentous bacilli, forming aerial hyphae, with colonies that may be pigmented, rough and without the BstEII digestion pattern in PRA-hsp65 method are suggestive of Nocardia spp. For a mycobacterial routine laboratory, a flow for the presumptive identification of Nocardia is essential, allowing the use of more accurate techniques for the correct identification, proper treatment and better quality of life for patients.